Students’ Perception of Using Mind Maps to Improve Students’ Writing Ability - Hanggrasawani, First Tista; Buana, Tetuka Yuma; Swari, Dayinta Resty Nindya; Nugrahaeni, Dwitiya Ari; Faradisa, Farikah (Journal of Education, Language Innovation, and Applied Linguistics, 2024)
This study aims to explore the students’ perception of using mind maps to improve their writing skills, especially in writing an article. The researcher also has a goal to find out the advantages of applying mind maps in learning writing. Qualitative methods are applied in this research. 28 students in the sixth semester of an academic writing course are the participants in this study. The data of this research are collected using a questionnaire. The questionnaire was designed with closed and open-ended questions. The average score of each statement in the close-ended question is classified as a good perception according to the interval score interpretation. The result of the open-ended question also showed a good perception from the participants. The study carefully analysed the acquired data using the approach indicated above. The qualitative analysis revealed strong themes about the students' perceptions towards mind maps as a tool for improving their article writing skills. These motifs were subsequently explored through extensive coding and thematic analysis. Furthermore, the study investigated the specific benefits that students perceived from incorporating mind maps into their writing process. Through in-depth interviews and textual analysis of open-ended responses, the researcher highlighted major benefits such as greater organisation, increased idea production, and increased clarity in communicating ideas in their papers. Moreover, the results of this study provided insight into the efficacy of mind maps as an educational tool in academic writing. The excellent reception and constructive feedback from participants highlighted mind maps' ability to encourage a more structured and coherent approach to writing, enabling the development of critical writing abilities required for academic achievement. Keywords: Advantages; Mind Map; Students’ Perception; and Writing Ability.